Nurse job task analysis: a profile of medical and surgical nursing activities. - Considine, Julie; Omonaiye, Olumuyiwa; Schlieff, Jordana; Boyd, Leanne (Australian Health Review, 2023)
Objective. We aim to examine the activities undertaken by medical and surgical ward nurses at a major health service in Victoria, Australia, to inform nursing and midwifery strategic workforce planning. Methods. This descriptive, exploratory study was conducted on 17 wards from three acute care hospitals in one of Victoria’s largest health services. The Work Observation Method by Activity Timing tool was used to enable participants to document the time spent in each of 10 nursing activity domains. Results. Data from 70 respondents across all shifts showed nurses spent one-third of their time in direct care. Registered nurses spent a lower proportion of time than enrolled nurses in direct care and medications overall. Compared with enrolled nurses, registered nurses spent less time in direct care on morning shifts and documentation on afternoon shifts, and more time on ward-related activities on afternoon shifts. Conclusions. Medical and surgical enrolled nurses and registered nurses spent comparable proportions of time engaged in specific activities. Further research is required to understand the influences on the time devoted to direct care and how time spent in direct care intersects with other activities, and the relationship with patient outcomes and quality of care indicators.